The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/1476127009349842
|View full text |Cite
|
Sign up to set email alerts
|

Striving toward the future: aspiration—performance discrepancies and planned organizational change

Abstract: Interest has been growing in understanding how organizations' aspiration levels affect their planning for future organizational change. Previous research has not specified whether organizations use direct competitors or other comparable organizations as referents for forming their aspirations. In this study, it is argued that organizations form their social aspirations based on two types of interorganizational comparisons: competitive and striving. In competitive comparisons, an organization compares its curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
127
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(149 citation statements)
references
References 76 publications
18
127
0
2
Order By: Relevance
“…A wide range of studies have examined the role of performance relative to historical and/or social aspirations on risk taking. In this literature, managerial risk taking has been operationalized as acquisitions (Audia & Greve, 2006;Greve, 2008Greve, , 2011Iyer & Miller, 2008;Kim, Finkelstein, & Haleblian, 2015), entrance into new markets (Barreto, 2012), innovation (Chen, 2008;Chen & Miller, 2007;Gaba & Bhattacharya, 2012;Gaba & Joseph, 2013;Greve, 2003;O'Brien & David, 2014;Vissa, Greve, & Chen, 2010), illegal behavior (Baucus & Near, 1991;Harris & Bromiley, 2007;Madsen, 2013), and organizational change (Arrfelt, Wiseman, & Hult, 2013;Baum & Dahlin, 2007;Greve, 1998;Labianca, Fairbank, Andrevski, & Parzen, 2009;Lant, Milliken, & Batra, 1992;Massini, Lewin, & Greve, 2005;Park, 2007). Most of these studies have found evidence supporting BTOF main-effect predictions of greater managerial risk taking after underperforming and lower levels of risk taking when over performing.…”
Section: The Behavioral Theory Of the Firm And Prospect Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of studies have examined the role of performance relative to historical and/or social aspirations on risk taking. In this literature, managerial risk taking has been operationalized as acquisitions (Audia & Greve, 2006;Greve, 2008Greve, , 2011Iyer & Miller, 2008;Kim, Finkelstein, & Haleblian, 2015), entrance into new markets (Barreto, 2012), innovation (Chen, 2008;Chen & Miller, 2007;Gaba & Bhattacharya, 2012;Gaba & Joseph, 2013;Greve, 2003;O'Brien & David, 2014;Vissa, Greve, & Chen, 2010), illegal behavior (Baucus & Near, 1991;Harris & Bromiley, 2007;Madsen, 2013), and organizational change (Arrfelt, Wiseman, & Hult, 2013;Baum & Dahlin, 2007;Greve, 1998;Labianca, Fairbank, Andrevski, & Parzen, 2009;Lant, Milliken, & Batra, 1992;Massini, Lewin, & Greve, 2005;Park, 2007). Most of these studies have found evidence supporting BTOF main-effect predictions of greater managerial risk taking after underperforming and lower levels of risk taking when over performing.…”
Section: The Behavioral Theory Of the Firm And Prospect Theorymentioning
confidence: 99%
“…Reflecting these concerns, caution that firm risk, often captured by accounting measures, may not reflect executives' attitudes and biases toward risk. In this regard, we encourage greater use of primary data to measure managers' risk behaviors and reference points (see, for example, Labianca et al, 2009;Larraza-Kintana et al, 2007;Massini et al, 2005;Singh, 1986). We recognize the difficulty of collecting primary data, but we believe that this approach, along with mixed methods (which are seldom used), will advance our understanding of managers' past, present and future reference points and attitudes toward risk taking.…”
Section: Future Research Opportunities and Challenges Across The Theomentioning
confidence: 99%
See 1 more Smart Citation
“…Firms risk taking involves new technology innovation and improvement, new products researches and development, new processes modification and reform, which will promote firms making significant technological advances and win the competitive superiority in markets (Labianca et al, 2009) [11]. The above R&D spending has long been deemed as highly risky investment, which represents firms input on innovation but accompanying higher uncertainty.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Finally, a number of studies, listed in the third column of table 1, have explicitly examined risky change, generally by considering multiple change decisions accompanied by varying levels of risk (i.e., Greve, 1998Greve, , 2003aLabianca et al, 2009). Greve's study of changes in radio station formats (1998) offers an excellent demonstration of risky change by clearly articulating levels of risk inherent in the different change decisions.…”
Section: Change and Risk In The Behavioral Theory Of The Firmmentioning
confidence: 99%